ҚОРАҚАЛПОҚ АНЪАНАЛАРИНИНГ ТАЪЛИМ-ТАРБИЯВИЙ МАЗМУНИ - Исмайлов, А.С. (SCIENCE and SOCIETY, 2024)
This article tells about the history, culture, traditions, national spirituality, unique national traditions and values, programs of the Karakalpak people.